The Effect Of The Triangle Training Method On Inside-Of-The-Foot Passing Skills In The Futsal Extracurricular Program At The Bengkulu Maritime And Fisheries Vocational High School - Mickey Ilhamy; Ajis Sumantri; Desrio Windoro (Educative Sportive, 2026)
This study aims to determine the effect of the triangle training method on the inside-of-the-foot passing skills of participants in the futsal extracurricular program at the Bengkulu Maritime and Fisheries Vocational High School. Passing is one of the most important basic techniques in futsal because it plays a role in maintaining possession, building attacks, and creating scoring opportunities. Based on the observation results, the passing ability of the extracurricular participants was still relatively low, characterized by a lack of passing accuracy, improper body positioning during passing, and minimal off-the-ball movement after passing. To address these issues, the triangle training method was implemented, which involves passing drills conducted in a triangular formation with continuous movement patterns and position exchanges. This study employed a quantitative method with a One-Group Pretest-Posttest design, whereby the participants’ skills were measured before and after the training intervention. The study population consisted of 30 futsal extracurricular participants from the Bengkulu Maritime and Fisheries Vocational School, who were also selected as the study sample using purposive sampling. The instrument used was an accuracy test for inside-of-the-foot passing. The intervention was administered over 16 sessions, after which the data were analyzed using normality tests, homogeneity tests, and a paired-sample t-test with the aid of SPSS software. The results of the study indicate an improvement in passing ability following triangle drills. Pretest scores fell into the low-to-moderate range, while posttest scores improved to the moderate-to-high range. Thus, the triangle drill method has a positive effect on improving inside-of-the-foot passing skills among participants in the futsal extracurricular program at the Bengkulu Maritime and Fisheries Vocational High School.